TO THE PROBLEM OF THE PEDAGOGICAL WORKERS’ MOTIVATION’S SYSTEM FORMING - Redko, S. I. (Continuing Professional Education: Theory and Practice, 2019)
The article considers the formation of the head of the institution of motivation teachers as a condition of their activities and performance of the entire teaching staff. The author emphasizes that the driving force of active work teachers are motivated, because just knowing what motivates teachers to actions that the motives underlying his work, you can develop an effective system of forms and methods of management of the institution. Understanding the essence of motivation and identify an implementation mechanism allows for efficient work management interaction in pedagogical work. Major emphasis is placed on ways to create a motivational monitoring as a key component of the system. Motivational monitoring will head the institution constantly track and monitor the status of work motivation teachers to its operative diagnosis and assessment of the dynamics, making qualified decisions. Finally, motivational monitoring activities will be effective only when based not on the means of administrative influence, and on the economic and sociopsychological levers, so the impact on the activities of the teacher will be in the mode of self regulation. Its implementation involves regular surveys teachers and analysis of the psychological information.